Sorghum grain, urea or soybean meal as a protein source in all-concentrate cattle finishing rations - G.A. Greathouse; R.W. Swanson; E.F. Smith; L.I. Smart; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1969)
Results of previous similar research have been reported in Kansas Agicu1tural Experiment Station Bulletins 483, 493, 507, and 518. Trials at several research centers and here have shown that roughage may be satisfactorily omitted from finishing rations for cattle often, reducing feed required per pound of gain. Cattle nay be finished on all-grain diets with only mineral and vitamin supplements when the grain has sufficient protein.
Keywords: Cattlemen' s Day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station); 529; Beef; Sorghum grain; Urea; Soybean meal; Finishing rations